Evaluation of corneal thickness with spectral-domain optical coherence tomography following keraring implantation for keratoconus: Five year follow-up - Eliaçık, Mustafa; Kırgız, Ahmet; Aygün, Beril (Taylor and Francis Ltd., 2020)
To evaluate the change in the position of intrastromal corneal ring segments (ICRS) implanted in keratoconus patients within five years of implantation. Participants in this study included keratoconus patients who received Keraring 10 ICRS implantation and had a follow-up time of at least 5 years. The distances from apex to anterior corneal surface (AA), from outer basal corner to posterior corneal surface (BP), and from inner basal corner to posterior corneal surface (CP) were measured at every postoperative visit (6 months, 1 year, 3 years, and 5 years) and compared to each other. Thirty eyes of 22 patients were included. The CP showed a statistically significant decrease at all 15 time points (p < .001); however, no statistically significant difference was found at 5 years regarding AA or BP (p > .05 for all). Triangular ICRS implanted in keratoconus patients remained stable for five years without any complications, which is an extremely important aspect of ICRS surgery. The only difference was a slight posterior movement of the inner basal corner, although without anterior chamber perforation.
Keywords: Keratoconus; Keraring Implantation; Corneal Thickness; Coherence Tomography